Comparison of the Unfolded Protein Response in Cellobiose Utilization of Recombinant Angel- and W303-1A-Derived Yeast Expressing β-Glucosidase - Zou, Shaolan; Jia, Yudie; He, Qing; Zhang, Kun; Ban, Rui; Hong, Jiefang; Zhang, Minhua (Frontiers in Bioengineering and Biotechnology, 2022)
The unfolded protein response (UPR) is one of the most important protein quality control mechanisms in cells. At least, three factors are predicted to activate the UPR in yeast cells during fermentation. Using UPRE-lacZ as a reporter, we constructed two indicator strains, KZ and WZ, based on Angel-derived K-a and W303-1A strains, respectively, and investigated their UPR response to tunicamycin, ethanol, and acetic acid. Then, four strains carrying plasmids BG-cwp2 and BG were obtained to realize the displaying and secretion of β-glucosidase, respectively. The results of cellobiose utilization assays indicated interactions between the UPR and the metabolic burden between the strain source, anchoring moiety, oxygen supply, and cellobiose concentration. Meanwhile, as expected, growth (OD600), β-glucosidase, and β-galactosidase activities were shown to have a positive inter-relationship, in which the values of the KZ-derived strains were far lower than those of the WZ-derived strains. Additionally, extra metabolic burden by displaying over secreting was also much more serious in strain KZ than in strain WZ. The maximum ethanol titer of the four strains (KZ (BG-cwp2), KZ (BG), WZ (BG-cwp2), and WZ (BG)) in oxygen-limited 10% cellobiose fermentation was 3.173, 5.307, 5.495, and 5.486% (v/v), respectively, and the acetic acid titer ranged from 0.038 to 0.060% (v/v). The corresponding maximum values of the ratio of β-galactosidase activity to that of the control were 3.30, 5.29, 6.45, and 8.72, respectively. Under aerobic conditions with 2% cellobiose, those values were 3.79, 4.97, 6.99, and 7.67, respectively. A comparison of the results implied that β-glucosidase expression durably induced the UPR, and the effect of ethanol and acetic acid depended on the titer produced. Further study is necessary to identify ethanol- or acid-specific target gene expression. Taken together, our results indicated that the host strain W303-1A is a better secretory protein producer, and the first step to modify strain K-a for cellulosic ethanol fermentation would be to relieve the bottleneck of UPR capacity. The results of the present study will help to identify candidate host strains and optimize expression and fermentation by quantifying UPR induction.